Hadith #2628 - Sunan Abi Dawud - Asyd bin 'Abdur Rahman أسيد بن عبد الرحمن الخثعمي; Frwh bin Mjahd; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة (Sunan Abi Dawud)
When the people encamped, (the narrator Amr ibn Uthman al-Himsi) said: When the Messenger of Allah (ﷺ) encamped, the people scattered in the glens and wadis. The Messenger of Allah (ﷺ) said: Your scattering in these glens and wadis is only of the devil. They afterwards kept close together when they encamped to such an extent that it used to be said that if a cloth were spread over them, it would cover them all.
Grade: Sahih

Hadith #2629 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Amr bin 'Uthman عمرو بن عثمان بن عفان; Asyd bin 'Abdur Rahman أسيد بن عبد الرحمن الخثعمي; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Frwh bin Mjahd (Sunan Abi Dawud)
I fought along with the Prophet (ﷺ) in such and such battles. The people occupied much space and encroached on the road. The Prophet (ﷺ) sent an announcer to announce among the people: Those who occupy much space or encroach on the road will not be credited with jihad.
Grade: Hasan